Factors Influencing Purchase Intention of Imported Skincare Products Mediated by Brand Image - Sherlin Sherlin; Immanuel Zai (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the effects of social media marketing, celebrity endorsement, Electronic-Word of Mouth (E-WOM), product quality, and price on purchase intention toward imported skincare products in Batam City, with brand image as a mediating variable. Methodology: A quantitative survey involving 207 users of imported skincare products in Batam City was conducted and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). Results: The findings indicate that social media marketing, E-WOM, celebrity endorsement, product quality, and price have positive and statistically significant effects on brand image (p < 0.05). Mediation analysis confirms that brand image significantly strengthens the indirect effects of these variables on purchase intention. Conclusions: Brand image plays a key role in enhancing consumers' purchase intentions by strengthening the impact of marketing efforts and product-related factors. A positive brand image builds trust and emotional connection, influencing consumer decisions and amplifying the effects of product quality, pricing, and promotions. Limitations: This study focuses on understanding the behaviours and preferences of consumers who purchase imported skincare products in Batam City, using a quantitative approach. By analysing numerical data, the research aims to identify key factors influencing consumer choices, such as product quality, pricing, and brand reputation, to provide insights into the demand for imported skincare products in the area. Contributions: The study provides empirical evidence and practical insights for developing integrated marketing strategies focused on strengthening brand image.